(untitled) (Baghdad Science Journal, 2023)
An easy, eclectic, precise high-Performance Liquid Chromatographic (HPLC) procedure was evolved and validated to estimate of Piroxicam and Codeine phosphate. Chromatographic demarcation was accomplished on a C18 column [Use BDS Hypersil C18, 5μ, 150 x 4.6 mm] using a mobile phase of methanol: phosphate buffer (60:40, v/v, pH=2.3), the flow rate was 1.1 mL/min, UV detection was at 214 nm. System Suitability tests (SSTs) are typically performed to assess the suitability and effectiveness of the entire chromatography system. The retention time for Piroxicam was found to be 3.95 minutes and 1.46 minutes for Codeine phosphate. The evolved method has been validated through precision, limit of quantitation, specificity, limit of detection linearity and accuracy. (LOD) was 1.92 mg/mL and (LOQ) was 6.336 mg/mL for Piroxicam, whereas (LOD) for Codeine phosphate was 0.29 mg/mL and (LOQ) was 0.95 mg/mL. Piroxicam and Codeine phosphate showed a linear signal in the domain of 5-50 µg/mL for each compound. This research presided to evolve and validate an HPLC method, and the proposed procedure can be used to estimate these drugs in their combined dosage forms.